The nature, causes and effects of contraband trade and capital between India and Sri Lanka - Sarvananthan, M. (Contemporary South Asia, 1999)
It is argued that studies of the complementary (a.k.a., alternate/black/hidden/ informal/irregular/parallel/second/shadow/subterranean/underground/unofficial) economy and contraband trade1 must supplement official national income and external trade data to get a more realistic state of any economy. This is especially important in developing countries where these may be pervasive. These studies will greatly enhance the effectiveness of policy formulation in many developing countries. Some may argue that due to the difficulties in gathering data on such illicit economic activities any estimation would be of questionable value and that policies formulated on such inaccurate data in turn may be inappropriate. However, I would argue that ignoring these illicit economic activities—which are significant in many countries—is to assign a zero value which is not satisfactory. Besides, in many developing countries, the official data on national income and external trade are itself of questionable nature2. Therefore, we cannot afford to be too concerned about the accuracy of the data. In most instances, we may have to deal with the second-best option. The present research concerns a quantitative estimation and a qualitative assessment of under-recorded, over-recorded and unrecorded exports, imports and capital flows; i.e., contraband trade and, by extension, capital as well, between India and Sri Lanka. This is the first ever study of contraband trade between these two neighbouring trading-partner countries. Further, this is the first ever study of both technical and physical contraband trade between any two countries. Hitherto, some economists have studied technical contraband trade (TCT) between a country and a group of trading partners (usually developed countries)3; and some anthropologists have studied physical contraband trade (PCT) between two or more trading partners,4 but no one has ever studied both